The role of steroids in the development of post-partum mental disorders - Paskova, Andrea; Jirak, Roman; Mikesova, Michaela; Adamcova, Karolina; Fartakova, Zdenka; Horakova, Vladimira; Koucky, Michal; Hill, Martin; Hruskovicova, Hana; Starka, Luboslav; Duskova, Michaela; Parizek, Antonin (Biomedical papers, 2014)
Background: Unfavorable post-partum changes to mental well-being affect more than half of all women, and are a risk to the health of both mother and baby. Their effects place strains on health and social systems. Currently, no generally accepted theory exists of the causes and mechanisms of post-partum mental disorders.Methods: Literature search up to 2012, using PubMed and search words: neuroactive steroids, post-partum mental disorders, depression, corticotropin-releasing hormone and estrogens.Results: There are several theories for post-partum depression. One is that autoimmune diseases are involved. Others revolve around genes responsible or that lead to increased disposition to the disorder. It is likely however that the process is associated with the separation of the placenta and the fetal zone of fetal adrenal gland, the main sources of corticotropin-releasing hormone and sexual and neuroactive steroids during pregnancy, and the ability of the receptor system to adapt to these changes. The central nervous system is able to produce neurosteroids, but the drop in levels of peripheral steroids likely leads to a sudden deficit in neuroinhibitory steroids modulating ionotropic receptors in the brain.Conclusions: Post-partum depression is a multifactorial disease with unknown etiology. It is probably associated with sudden changes in the production of hormones influencing the nervous system, and on the other hand the ability of the receptor system to adapt to these changes. When the relative changes in concentrations of hormones, rather than their absolute levels, is likely more important.
Keywords: neuroactive steroids; postpartum depression; corticotropin-releasing hormone; estrogens; allopregnanolone